1991
DOI: 10.1037/0021-843x.100.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and symptomatology among adolescent children of alcoholics.

Abstract: This study assessed the magnitude and specificity of parental alcoholism as a risk factor for internalizing symptomatology, externalizing symptomatology, and alcohol and drug use in adolescence. We evaluated parents' and children's reports of symptomatology and children's reports of alcohol and drug use in a community sample of 454 adolescents. The results showed that parental alcoholism was a moderate to strong risk factor, with stronger risk associated with recent (rather than remitted) parental alcoholism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
380
8
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 453 publications
(417 citation statements)
references
References 44 publications
23
380
8
3
Order By: Relevance
“…Alternatively, and more specific to the focus of the current study, internalizing symptoms may too narrowly define child functioning to capture the ways in which COAs respond to those periods of life when their parents are actively abusing alcohol. This possible explanation is consistent with previous studies showing that the strongest specific effects of parent alcoholism on child functioning indices are, not surprisingly, for alcohol involvement itself (Chassin et al 1991). Moreover, we might expect the timevarying and proximal effects of parent alcoholism on children's externalizing symptoms to be more evident even in childhood because externalizing symptoms consistently show stronger relations with alcohol involvement than do internalizing symptoms (e.g., Hussong et al 1998).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Alternatively, and more specific to the focus of the current study, internalizing symptoms may too narrowly define child functioning to capture the ways in which COAs respond to those periods of life when their parents are actively abusing alcohol. This possible explanation is consistent with previous studies showing that the strongest specific effects of parent alcoholism on child functioning indices are, not surprisingly, for alcohol involvement itself (Chassin et al 1991). Moreover, we might expect the timevarying and proximal effects of parent alcoholism on children's externalizing symptoms to be more evident even in childhood because externalizing symptoms consistently show stronger relations with alcohol involvement than do internalizing symptoms (e.g., Hussong et al 1998).…”
Section: Discussionsupporting
confidence: 68%
“…Direct interview data confirmed that neither biological nor custodial parents met criteria for a lifetime alcoholism diagnosis. Recruitment biases have been found to be minimal (Chassin et al 1991(Chassin et al , 1992. Although contact rates were low (38.3% from archival records and 44.2% from reverse directories), participation rates were high (72.8% of eligible COA families and 77.3% of eligible control families participated).…”
Section: Samples and Proceduresmentioning
confidence: 91%
See 2 more Smart Citations
“…Parental substance abuse is often associated with family dysfunction, as the parenting skills and behaviours of adults with such problems are significantly impaired. Substance abusing parents can frequently be neglectful, abusive, unreliable, and emotionally unavailable for their children (Chassin, Rogosch, & Barrera, 1991; Velleman, Templeton, Reuber, Klein, & Moesgen, 2008). Children who are subjected to this kind of dysfunctional family situation, summarized in the concept of “Adverse Childhood Experiences” (ACE; Felitti et al, 1998), are at risk for developing problematic behaviours that affect both their own and their future children’s lives (Ivarsson, Saavedra, Granqvist, & Broberg, 2015; Kalmakis & Chandler, 2015; Lomanowska, Boivin, Hertzman, & Fleming, 2015).…”
Section: Introductionmentioning
confidence: 99%